2007
DOI: 10.1182/blood-2006-08-040774
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombin Cambridge II (A384S): an underestimated genetic risk factor for venous thrombosis

Abstract: The antithrombin A384S mutation has a relatively high frequency in the British population but has not been identified in other populations. This variant has been associated with cases of thrombotic disease, but its clinical relevance in venous thrombosis remained unclear. We have conducted a secondary analysis of the prevalence of the mutation in a large case-control study, including 1018 consecutive Spanish patients with venous thromboembolism. In addition, we evaluated its functional consequences in 20 carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 26 publications
0
76
0
4
Order By: Relevance
“…The identification and analysis of natural mutations in patients with antithrombin deficiency have assisted the description of key functional domains or residues of this anticoagulant (15)(16)(17)(18)22). Thus, mutations at the RCL, HBS, and the C-sheet are responsible for the three subtypes of antithrombin type II deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The identification and analysis of natural mutations in patients with antithrombin deficiency have assisted the description of key functional domains or residues of this anticoagulant (15)(16)(17)(18)22). Thus, mutations at the RCL, HBS, and the C-sheet are responsible for the three subtypes of antithrombin type II deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For the diagnosis of a RDVT, different CUS criteria are established. [2][3][4]. Previous studies have validated these criteria for the diagnosis of RDVT by CUS, but there is a lack of data in the literature reporting the daily practise of diagnosing clinically suspected ipsilateral RDVT [2][3][4].…”
mentioning
confidence: 95%
“…Moreover, whether the AT Cambridge II mutation increases the risk of VT remains doubtful. Initially, this mutation was described in asymptomatic subjects from the UK [2,3]; in contrast, subsequent findings from a large Spanish case-control study [4] suggested that the mutation may be a VT risk factor and the most frequent cause of AT deficiency in Caucasian populations. However, results obtained in three independent large French cohorts [5,6] are not in agreement with this hypothesis.…”
mentioning
confidence: 99%
“…As the reactive site of thrombin and FXa differs somewhat, one would expect that AT deficiencies caused by certain mutations around the reactive site are detected by the two types of assays with different sensitivity. Indeed, the Ala384Ser mutation (AT Cambridge II) which is a relatively prevalent variant in the general population, is not detected by the anti-FXa assay, but anti-thrombin activity is mildly, but significantly, reduced (63,64). However, this mutation causes only a relatively mild thrombophilia, and even elderly homozygous individuals might lack the history of VTE.…”
Section: Laboratory Diagnosis Of Antithrombin Deficiencymentioning
confidence: 99%
“…However, there is at least one notable exception. The heterozygous p.Ala384Ser mutation (AT Cambridge II) causes type II RS deficiency with a mild phenotype, and this mutation can also exist in homozygous form (63,64). Type II HBS deficiency confers a lower risk of thrombosis compared with the other subtypes (65,66).…”
Section: Molecular Genetic Background Of Antithrombin Deficiency Genmentioning
confidence: 99%